Islamic Education Adaptation to Sociocultural Changes in the Globalization Era - Erihadiana, Mohamad; Rustandi, Feri; Munawaroh, Cucu; Roswan Pauzi, Ali (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
Globalization presents significant challenges for Islamic education, especially in maintaining its identity amid modernization and global demands. This study uses a descriptive-analytical qualitative approach with a literature study method, utilizing secondary data sources such as academic journals, books, and relevant articles from platforms such as Google Scholar and Scopus. This study aims to analyze the adaptation strategy of Islamic education to sociocultural changes in Indonesia's globalization era. Data were collected through a literature review and analyzed using a thematic approach to identify key patterns such as globalization's impact, educational institutions' challenges, and the integration of Islamic values in education. The study's findings show that Islamic education faces the challenges of globalization, especially in maintaining the relevance of traditional Islamic values. The main strategy is digitalizing learning and adaptive curriculum based on Islamic values. Educator training and cross-sector collaboration are important to improve the competitiveness of Islamic education. The optimal use of technology allows Islamic education to remain inclusive and competitive globally. Islamic education can maintain its identity while contributing to creating a global society that is fair, inclusive, and based on Islamic values.